2007
DOI: 10.1021/ac071187g
|View full text |Cite
|
Sign up to set email alerts
|

General Microarray Technique for Immobilization and Screening of Natural Glycans

Abstract: We here present a printed covalent glycan microarray for protein-binding studies, using low-femtomole quantities of glycans. Glycans, either natural glycans, which were released from glycoproteins and glycolipids from natural sources, or synthetic glycans, were labeled with common fluorescent labels (e.g., 2-aminobenzamide or 2-aminobenzoic acid) by reductive amination and purified by HPLC. The purified glycoconjugates were covalently immobilized on commercial epoxide-activated glass slides via the secondary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 24 publications
(48 reference statements)
3
102
0
Order By: Relevance
“…These global profiling studies have confirmed the major glycan structures previously identified and provided new information on the diversity of glycans and the heterogeneity found among the life stages of the parasite and their secretions (27,(29)(30)(31). Several studies also have demonstrated the feasibility of profiling schistosome glycans using various microarray printing technologies and probing with glycan-binding proteins, antibodies, and antisera, demonstrating that such techniques can be powerful tools for profiling the immune response to this disease (26,(32)(33)(34) and the development or characterization of novel anti-glycan reagents. The combination of these techniques, i.e., glycomics and/or glycan structural profiling, which is guided by the use of immunologically relevant reagents, such as antisera and MAbs, has great potential to improve our understanding of the anti-glycan response and uncover novel, immunologically relevant diagnostic and vaccine candidates.…”
supporting
confidence: 58%
“…These global profiling studies have confirmed the major glycan structures previously identified and provided new information on the diversity of glycans and the heterogeneity found among the life stages of the parasite and their secretions (27,(29)(30)(31). Several studies also have demonstrated the feasibility of profiling schistosome glycans using various microarray printing technologies and probing with glycan-binding proteins, antibodies, and antisera, demonstrating that such techniques can be powerful tools for profiling the immune response to this disease (26,(32)(33)(34) and the development or characterization of novel anti-glycan reagents. The combination of these techniques, i.e., glycomics and/or glycan structural profiling, which is guided by the use of immunologically relevant reagents, such as antisera and MAbs, has great potential to improve our understanding of the anti-glycan response and uncover novel, immunologically relevant diagnostic and vaccine candidates.…”
supporting
confidence: 58%
“…Thus, in a method developed by de Boer et al (2007), glycans released from glycoproteins or glycolipids, both from natural sources or synthetic material, were labeled by reductive amination with common fluorescent labels such as 2-AB or 2-aminobenzoic acid (2-AA, 1/57) purified by HPLC and characterized by MALDI-TOF or MALDI-TOF/TOF MS from DHB or ATT. The purified glycoconjugates were covalently immobilized on commercial epoxide-activated glass slides via the secondary amine group that linked the glycan moiety with the fluorescent tag.…”
Section: Glycan Arraysmentioning
confidence: 99%
“…In the past decade, several glycan microarrays have been developed to investigate the binding between CBPs and glycans [1][2][3][4][5][6][7][8][9]. These arrays make use of printed glycan slides in combination with fluorescence detection, and differ mainly in the way the glycans are immobilized, as reviewed by Culf et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…We here present an SPR-based glycan microarray using the Biacore Flexchip apparatus for screening of interactions between glycans and proteins, which methodology is comparable with our recently developed glass slide glycan microarray [8]. Glycans are labeled by reductive amination with conventional fluorescent tags, e.g.…”
Section: Introductionmentioning
confidence: 99%